Introduction to the Development of Skin in Vertebrates - Lorenzo Alibardi (Journal of Developmental Biology, 2023)
The integument of vertebrates is a complex and large organ positioned at the interface with the aquatic or terrestrial environment, and is derived from the embryonic ectoderm (epidermis) and mesoderm (dermis and hypodermis) [...]